A viscoelastic poromechanical model for shrinkage and creep of concrete. (March 2020) - Aili, Abudushalamu; Vandamme, Matthieu; Torrenti, Jean-Michel; Masson, Benoit
Abstract: Long-term delayed strain of concrete impacts the lifetime of civil engineering structures such as dams, nuclear power plants, nuclear waste storage tunnels or large bridges. In design practice, the long-term delayed strain of concrete is decomposed into four components: autogenous shrinkage, basic creep, drying shrinkage and drying creep. The four components are first computed separately and then summed up to obtain the total delayed strain of concrete, without wondering about any potential correlation between them. In this work, we aim at modeling the total delayed strain in a unified manner, without assuming this decomposition a priori. Such model is derived in the framework of viscoelastic poromechanics. The influence of relative humidity on the creep properties is taken into account. We assume that drying creep is due to the fact that the mechanical consequences of capillary effects are larger in loaded drying specimens than in non-loaded drying specimens. The model is validated by comparing the prediction with experimental results of delayed strain from the literature and discussed with respect to existing models.